PENGGUNAAN EJAAN YANG DISEMPURNAKAN DALAM PP NOMOR 32 TAHUN 2013 TENTANG STANDAR NASIONAL PENDIDIKAN - Ilham Hapadean; Hasnah Faizah AR; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research entitled The Use of Improved Spelling in Government Regulation No. 32 Year 2013 on National Education Standards. This research aims to determine the percentage of the correct use of capital letters, the percentage of correct use of dot, and the percentage of the correct use of commas which contained in Government Regulation No. 32 Year 2013 on National Education Standards. The method used was descriptive method with qualitative and quantitative approaches. The data of this research was the verses that contain capital letters, dots and commas, which is contained in each chapter of Government Regulation No. 32 Year 2013 on National Education Standards. The result of the research shown at the accuracy of capitalization was 57.8%, the accuracy of the use of dots was 98.2%, and accuracy of commas was 91.3%. From these three uses of the spelling that has been investigated, the spelling which has the largest percentage of accuracy was the use of dots, at 98.2% and the smallest is the percentage of the correct use of capital letters, at 57.8%.Key words: Government Regulation No.32 Year 2013, Improved Spelling, Capital Letter, Dot, Commas, Accuracy Percentage.